FAKTOR-FAKTOR PENYEBAB RESIKO JATUH PADA PASIEN DI BANGSAL NEUROLOGI RSUP DR. M DJAMIL PADANG - - Julimar (LPPM Universitas Muhammadiyah Riau, 2018)
The risk of falling is possible for someone to fall which can cause physical injury that is generally caused by environmental and physiological factors that can result in injury. The incidence of the risk of falls that occurred in the Hospital Dr. M Djamil in 2015 as much as 0.5%. The incidence of the risk of falling inIndonesia in January to September 2012 amounted to 14%. The high likelihood that a patient runs the risk of falling is influenced by several factors, one of which factors from the patient's own. The purpose of this study to find out what are the factors that greatly affect the safety of patients, especially in thedepartment of neurology ward. Dr. M Djamil Padang. This research was conducted in July-August 2016 for the department. Dr. M Djamil Padang. This research uses descriptive analytical method. The population in this study were nurses who are specifically in the department of Neurology ward. Dr. M Djamil Padang with a sample size of 16 people were taken by total sampling. Data collection tool is a questionnaire. Processing of data by editing, coding, data entry, and tabulating. Analysis of the data used univariate data analysis. The results of this study found that the factors that cause the risk of falls in patients include: more than half (75%) of respondents rate the organization and management of high factor, more than half (68.75%) of respondents valued the work environment factors, most of all (94%) of respondents rated high factor of the team, more than half (75%) of respondents rated higher personnel factor, less than half (37.5%) of respondents low duty factor, all (100%) of respondents rated high patient factors, and more than half (56.25%) of respondents low rate communication factor. For nurses who value high ratings may be influenced by the style of good leadership in taking any decision, the existence of good cooperation between the heads of the room with the nurse, and their examination environment around the patient. Researchers suggested that nurses still maintain good performance in carrying out its duties and researchers expect that number causes the risk of falling in the neurology ward, especially Hospital Dr. M Djamil Padang reduced.